A facile cathode design with a LiNi0.6Co0.2Mn0.2O2 core and an AlF3-activated Li1.2Ni0.2Mn0.6O2 shell for Li-ion batteries. (1st March 2018) - Hu, Guorong; Qi, Xianyue; Hu, Kaihua; Lai, Xiangwan; Zhang, Xiang; Du, Ke; Peng, Zhongdong; Cao, Yanbing
Abstract: Ni-rich ternary cathode materials have attracted great attention because of its high energy density, good cycle performance and high rate performance. However, it suffers from the poor electrochemical performance at elevated temperature and high cut-off voltage due to intrinsic grievous side effects. Herein, a core-shell structure of LiNi0.6 Co0.2 Mn0.2 O2 as the core and Li1.2 Ni0.2 Mn0.6 O2 as the shell which integrated the structural stability of Ni-rich materials and the surface chemical stability of Li-rich materials was purposefully designed via a polyvinyl pyrrolidone (PVP)-assisted sol-gel method and a novel chemical activation for the Li-rich shell with AlF3 treatment. Research by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy methods (TEM), and energy dispersive X-ray spectrometer (EDS) have been proved that the surface of the host materials was deposited with a uniform shell layer of Li1.2 Ni0.2 Mn0.6 O2 and AlF3 particles. As a result, the core-shell materials displayed excellent cycle performance: 94.0% capacity retention after 100 cycles (2.0–4.5 V under 1C and 25 °C) especially at high temperature≈50 °C: 86.5% capacity retention.